Sound transmission through floor/ceiling assemblies - Warnock, A.C.C. (Canadian Acoustics, 1998)
The airborne and impact sound transmission through typical floor constructions used in Canadian housing were studied. About 200 different floor variations were included in the study. Joist types included solid wood, steel, wood I-joists and wood trusses. A few joist floors with concrete toppings and three concrete slabs were also tested. Results show that the major factor controlling the sound insulation of a given type of cavity floor is the sum of the masses per unit area of the floor and ceiling layers. Increasing the thickness and density of the sound absorbing material, the depth and spacing of the joists and the spacing of resilient metal channels increases sound insulation.